Pengaruh Store Atmosphere, Kualitas Pelayanan, Harga Dan Location Attractiveness terhadap Keputusan Pembelian di Historica Coffee and Kitchen Surabaya - Muhammad Alvin Syihabuddin; Rita Ambarwati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the influence of Store Atmosphere, Service Quality, Price and Location Attractiveness on Purchase Rate at Historica Coffee and Kitchen Surabaya. This research uses the Quantitative method. The type of data research used is primary data obtained based on distribution to 100 respondents. Sampling used using non-probability with purposive sampling technique with the criteria of consumers who have made purchases at Historica Coffee and Kitchen Surabaya. The data analysis method is carried out using multiple linear regression analysis. The test results show that the variables of Store Atmosphere, Service Quality, Price and Location Attractiveness have a positive effect on the Purchase Decision at Historica Coffee and Kitchen Surabaya.